Mechanical characterization and modeling of an innovative composite material for railway applications. (February 2017) - Genovese, A; Russo, M; Strano, S
The innovation in the railway industry is focused on the production of lightweight vehicles with high performance, in order to obtain an energy power saving and to satisfy the environmental and global community requests. To pursue this aim, new materials have been increasingly used for vehicle structures. The selection of innovative materials and the definition of the relative properties represent, however, one of the most critical aspects for the design. Several factors, such as technical requirements, strength- and stiffness-to-weight ratios, crash resistance, and cost, are involved in material selection for rail vehicles. In addition, materials have to be chosen in accordance with the reference standards concerning fire resistance. This paper describes the activity carried out in order to acquire the needed information about selected composite materials to be used in the design and validation phases for a structural rail vehicle end and a roof. The material under investigation has been manufactured in order to satisfy the strict railway light metro fire normative. Due to the novelty of the adopted composite materials, a full mechanical characterization of the lamina was needed. The orthotropic material properties were verified and tuned using further tests on laminate and sandwich configurations in order to take into account, also, the influence of manufacturing process parameters. Analytical and numerical approaches have been used to validate and optimize the structural layout. Results of the multistep material characterization, acquired during the above phases, have been used to perform computational analysis in order to further improve the component design.